2020
DOI: 10.1177/1534735420924094
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic and Circadian Effects of Small Molecules Directly and Indirectly Targeting the Core Circadian Clock

Abstract: Circadian rhythms are essential for controlling the cell cycle, cellular proliferation, and apoptosis, and hence are tightly linked to cell fate. Several recent studies have used small molecules to affect circadian oscillations; however, their concomitant cellular effects were not assessed, and they have not been compared under similar experimental conditions. In this work, we use five molecules, grouped into direct versus indirect effectors of the circadian clock, to modulate periods in a human osteosarcoma c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…By contrast, no significant differences were observed in the percentage of wound closure between cultures treated with PF670462 (1.5 μM) or KL001 (25.4 μM) and control cells. In this connection, Lin and collaborators showed that KL001 (12 μM) or PF670462 (1.5 μM) treatment for 24 h did not significantly affect cancer cell migration compared to osteosarcoma non-treated cells [52]. Reports in the literature support our results, suggesting that GSK-3 has a key role in regulating epithelialmesenchymal transition (EMT) in prostate and bladder tumors (reviewed in [28]).…”
Section: Discussionsupporting
confidence: 84%
“…By contrast, no significant differences were observed in the percentage of wound closure between cultures treated with PF670462 (1.5 μM) or KL001 (25.4 μM) and control cells. In this connection, Lin and collaborators showed that KL001 (12 μM) or PF670462 (1.5 μM) treatment for 24 h did not significantly affect cancer cell migration compared to osteosarcoma non-treated cells [52]. Reports in the literature support our results, suggesting that GSK-3 has a key role in regulating epithelialmesenchymal transition (EMT) in prostate and bladder tumors (reviewed in [28]).…”
Section: Discussionsupporting
confidence: 84%
“…By contrast, no significant differences were observed in the percentage of wound closure between cultures treated with PF670462 (1.5 μM) or KL001 (25.4 μM) and control cells. In this connection, Lin and collaborators showed that KL001 (12 μM) or PF670462 (1.5 μM) treatment for 24 h did not significantly affect cancer cell migration compared to osteosarcoma non-treated cells (Lin et al 2020 ). Reports in the literature support our results, suggesting that GSK-3 has a key role in regulating epithelial-mesenchymal transition (EMT) in prostate and bladder tumors (reviewed in (Sahin et al 2019 )).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of PER and CRY and their heterodimerization in the evening prevent the activity of BMAL1 and CLOCK. Therefore, a rhythmic oscillation occurs within a period of about 24 h 36 …”
Section: Links Between Circadian Clock and Covid‐19mentioning
confidence: 99%
“…35 Accumulation of PER and CRY and their heterodimerization in the evening prevent the activity of BMAL1 and CLOCK. Therefore, a rhythmic oscillation occurs within a period of about 24 h. 36 The circadian clock is involved in regulating many physiological processes in the body. 37 A healthy individual has a synchronized circadian clock system working in harmony between the central and peripheral clocks.…”
Section: Links Between Circadian Clock and Covid-19mentioning
confidence: 99%